Effectiveness of the Mat Pilates on the postural control, plantar pressure and plantar arch of school children: A randomized clinical trial. (October 2021) - Neves, Jessica Caroliny de Jesus; Valenciano, Paola Janeiro; Cibinello, Fabíola Unbehaun; Carvalho, Mônica Yosino Leão; Fujisawa, Dirce Shizuko
Abstract: Objective: To evaluate the effectiveness of Mat Pilates on postural control, plantar pressure and plantar arch (ALM) in schoolchildren. Design and setting: The study was a randomized clinical trial, developed at the Early Childhood Education Institute, Londrina-PR. The participants were randomly assigned to groups: Pilates Group (PG) and Control Group (CG). Patients in the CG did not perform extra physical activity (Interventions). Participants: 43 children (eight to 12 years), no prior knowledge of the Pilates method, and no exercise training in the last six months. Intervention: The exercise program was based on the Mat Pilates method, twice weekly, 50 min each, 28 sessions. Outcome measures: Static balance (force platform), dynamic balance (the Reach Test), ALM (plantigraphy) and plantar pressure (baropodometry). The assessors were blinded to the allocation of participants. Results: Three children were excluded before randomization and 40 were randomized (PG n: 20; CG n:20).12 children were excluded during the protocol (PG n:7; CG n:5) and included in the intention to treat analysis. No significant difference between groups was observed for static and dynamic balance and ALM measures. There was a significant difference in the following outcomes for the PG: the plantar pressure on the right hemibody forefoot between pre-test 38.70 ± 14.38 and post-test 42.65 ± 15.63 (ES = 0.66; SRM = 0.50). The plantar pressure on the right hemibody rearfoot between pre-test 61.10 ± 14.18 and post-test 56.85 ± 19.39 (ES = 0.68; SRM = 0.53). No adverse or harmful events were reported in any group. Conclusion: There were no differences in static and dynamic postural control and ALM between PG and CG. However, children GP showed improvement in some results of plantar pressure in relation CG. Clinical trial registration number: Brazilian Registry of Clinical Trials (REBEC) (N_ RBR-8t5p7d).